Uncommon genetic syndromes and narrative production - Case Studies with Williams, Smith-Magenis and Prader- Willi Syndromes - Garayzábal Heinze, Elena (2012)
This study compares narrative production among three syndromes with genetic microdeletions: Williams syndrome (WS), Smith-Magenis syndrome (SMS), and Prader-Willi syndrome (PWS), characterized by intellectual disabilities and relatively spared language abilities. Our objective is to study the quality of narrative production in the context of a common intellectual disability. To elicit a narrative production, the task Frog! Where Are You was used. Then, structure, process, and content of the narrative process were analysed in the three genetic disorders:WS (n52), SMS (n52), and PWS (n52). Data show evidence of an overall low narrative quality in these syndromes, despite a high variability within different measures of narrative production. Results support the hypothesis that narrative is a highly complex cognitive process and that, in a context of intellectual disability, there is no evidence of particular ‘hypernarrativity’ in these syndromes.